Towards A Competency Framework for SME Accountants - A South African Perspective (Global Journal of Management and Business Research, 2014)
Globalization has brought major changes in the world economy, for example a significant increase in trade and investments, rapid technological changes in communications as well as an increasing trend towards deregulation of financial markets. Prospects of increased sales in the world-wide market did not necessarily pose the same benefits to all market participants. In contrast to large multi-national companies, the traditional focus of Small and Medium Enterprises (SMEs) did not include exporting and importing along with alliances, branches and joint ventures abroad. Despite the pivotal roles of small and medium businesses in many economies, the specific challenges resulting from the globalisation phenomenon cannot be denied.
Keywords: competency framework; international federation of accountants; south africa institute of professional accountants; iaesb; ies